Nusantara Animation Reconstruction Based on the Shakyamuni Archery Relief from Borobudur - Ferric Limano; Lintang Widyokusumo (Journal of Urban Society's Arts, 2026)
This research aims to develop an animation concept (moving image) inspired by Nusantara, which can serve as a source of inspiration for Indonesian animation and offer a unique value in the global market. The object of study used to derive this concept is the Lalitavistara relief depicting Shakyamuni drawing a bow at Borobudur. This particular relief was chosen because the depiction of Shakyamuni’s pose conveys a sense of movement. The method employed to generate this Nusantara animation concept is Design-Based Research (DBR) in animation. The character’s motion was reconstructed from the relief poses using a biped rigging system in 3DS Max. To accurately interpret Shakyamuni’s pose, the researcher utilized 3D photogrammetry to capture clear and detailed visuals of the character’s posture. The motion reconstruction process involved creating a sequence of character poses, starting from key poses to blocking poses, ultimately resulting in a reconstructed animation inspired by Nusantara. The findings of this research reveal that the main archery movement is not portrayed directly; instead, it incorporates additional movements that enhance the aesthetic value—specifically, dance-like gestures embedded within the primary action. Furthermore, some of these choreographed poses carry implicit meanings within their motions. Therefore, the resulting Nusantara animation concept can serve as a valuable reference for future Indonesian animated film productions, offering a distinctive and culturally rich identity in the global animation market.